Layer-by-layer plasma enhanced chemical vapour deposition of nanocrystalline silicon thin films / Goh Boon Tong - Goh, Boon Tong (2012)
This work is focused on the study of hydrogenated silicon (Si:H) thin films and nanostructures grown by layer-by-layer (LBL) deposition technique using a home-built radio-frequency (rf) plasma enhanced chemical vapour deposition (PECVD) system. The initial phase of this work involved preparation and characterization of hydrogenated silicon (Si:H) thin films by continuous (CD) and LBL deposition techniques on crystal silicon (c-Si) and glass substrates at different rf powers, substrate temperatures and hydrogen to silane flow-rate ratios. The effects of the deposition conditions on the optical and structural properties of the films are studied by optical transmission spectroscopy, Fourier transform infrared (FTIR) spectroscopy and X-Ray diffraction (XRD). The influence of substrates on these properties is also investigated. The second phase is focused on the study of the morphology, crystallinity, crystallite size, siliconoxygen bonding and photoluminescence (PL) properties of the Si:H films grown on c-Si substrates by LBL deposition technique at the same deposition conditions in the first phase. These properties of the films are characterized by Micro-Raman scattering spectroscopy, field emission scanning electron microscopy (FESEM), high resolution transmission electron microscopy (HRTEM) and Micro-photoluminescence spectroscopy including further analysis done on the characterization results obtained from XRD and FTIR measurements done in the first phase in this work. The results of this work demonstrated that rf power and substrate temperature produced significant changes to the optical and structural properties of the LBL films compared to the CD films. Increase in rf power increased the deposition rate of the LBL and vice-versa for the CD films. Also, increase in rf power increased the disorder of the CD films however suppressed the disorder in the LBL films. The preferred crystalline orientation was also changed from Si (311) to Si (111) plane with increase in rf power. Increase in substrate temperature increased the deposition rate, refractive index and structural order in the LBL films. The substrate temperature showed significant effects on optical band gap and hydrogen content in the LBL films. The LBL films deposited at substrate temperatures of 100 and 200°C showed large optical energy gaps suggesting that broadening of the band gap was due to quantum confinement effects. The LBL films deposited on c-Si substrates showed highly crystalline structure as compare to the other deposited films. The periodic hydrogen plasma treatment on the growth surface of the film during the LBL deposition processes showed effectively enhances the electrooptical properties of these LBL films. The LBL deposition produced silicon nanostructures with Si nano-crystallites embedded in either amorphous silicon (a-Si) or mixed phases of a-Si and amorphous silicon oxide (a-SiO) matrix for the films deposited on c-Si substrates. These nanostructures of nanocrystalline silicon (nc-Si) grains produced high intensity of PL emission due to enhancement of quantum confinement effects by the presence of high crystalline volume fraction (XC ~ 41-54 %) of Si nano-crystallites (~ 2 nm) in the matrix. The intensity of the PL emissions was strongly dependent on crystalline volume fraction, crystallite size and oxygen content in the a-SiO matrix. These parameters were significantly controlled by the rf power and substrate temperature. Based on these results, the growth kinetics and structural configuration of the LBL grown nc-Si grains were proposed. It was shown that high intensity of PL emission was emitted by these clusters of nc-Si grains.